Management of pregnancy and labor in female with combination of homozygous Leiden and heterozygous prothrombin G20210A mutations - M. O. Arslanbekova (Акушерство, гинекология и репродукция, 2020)
Here we describe a clinical case of successfully managed pregnancy and labor in female with multigenic thrombophilia (combination of homozygous Leiden and heterozygous prothrombin G20210A mutations) associated with high risk of thrombosis by using proper anticoagulant therapy. It was underlined that females with obstetric complications should be examined for inherited and acquired types of thrombophilia.